Sex peptide of Drosophila melanogaster males is a global regulator of reproductive processes in females. - Gioti, A; Wigby, S; Wertheim, B; Schuster, E; Martinez, P; Pennington, C; Partridge, L; Chapman, T (2012)
Seminal fluid proteins (Sfps) alter female behaviour and physiology and can mediate sexual conflict. In Drosophila melanogaster, a single Sfp, the sex peptide (SP), triggers remarkable post-mating responses in females, including altered fecundity, feeding, immunity and sexual receptivity. These effects can favour the evolutionary interests of males while generating costs in females. We tested the hypothesis that SP is an upstream master-regulator able to induce diverse phenotypes through efficient induction of widespread transcriptional changes in females. We profiled mRNA responses to SP in adult female abdomen (Abd) and head+thorax (HT) tissues using microarrays at 3 and 6 h following mating. SP elicited a rich, subtle signature of temporally and spatially controlled mRNAs. There were significant alterations to genes linked to egg development, early embryogenesis, immunity, nutrient sensing, behaviour and, unexpectedly, phototransduction. There was substantially more variation in the direction of differential expression across time points in the HT versus Abd. The results support the idea that SP is an important regulator of gene expression in females. The expression of many genes in one sex can therefore be under the influence of a regulator expressed in the other. This could influence the extent of sexual conflict both within and between loci.